AMBIGUITAS POSISI: GELANGGANG, ASRUL SANI, DAN “SAHABAT SAYA CORDIAZ” - Muhammad Qadhafi (Kantor Bahasa Provinsi Maluku Utara, 2022)
This article aims to reveal the hidden aspects behind the ambiguity of the positions of Gelanggang, Asrul Sani, and the narrator of “Sahabat Saya Cordiaz”. This study uses qualitative data collection methods. The researcher uses the Bourdieu’s field construction method and the Social Network Visualizer (SocNetV) application to visualize the structure. The results of this study indicate that there is a similar doxa of Gelanggang and Pujangga Baru behind the ambiguity of Gelanggang’s position; behind the ambiguity of Asrul Sani's position lies the multiple-role relation and distance from absolutes that fits the doxa of Gelanggang; and the ambiguity of the narrator's position is homologous to the ambiguity of Gelanggang’s position and Asrul Sani's position. The alignment between Gelanggang, Asrul Sani, and “Sahabat Saya Cordiaz” shows that the objective structure has a mutual relationship with the author's subjective structure which is manifested through his literary works.